Taxonomic status of Talides basistrigata Eaton, 1932 (Lepidoptera, Hesperiidae) and its reinstatement based on an integrative assessments - Lazo-Rivera, Ana (2023)
Talides basistrigata Eaton, 1932, originally described from Peru, was subsequently transferred to the genus Hylephila Billberg, 1820 by Evans (1955) and considered a subspecies of H. phyleus (Drury, 1773), arguing that basistrigata inhabits drier environments than phyleus. Currently, the taxonomic status proposed by Evans is retained. The aim of this study is to reinstate the taxonomic status of valid species for basistrigata based on an integrative analysis considering morphological, ecological, and genetic aspects. Genitalic structures were examined in specimens of both basistrigata and phyleus, mitochondrial COI gene sequences were obtained for both species, and field data were collected to understand their oviposition behaviour in the vicinity of Arequipa city, southwestern Peru. As a result of the morphological examination, notable differences were found between the male genitalia structures of both species, primarily in the caudal processes of the valvae, the arrangement of the pectines, and the shape of the uncus. Regarding the genetic analysis, a genetic distance of greater than 3% was observed between the two species, thus supporting the taxonomic status of species for basistrigata. Additionally, from an ecological perspective, it was recorded that both species employ distinct oviposition mechanisms and different host plants, exhibiting spatial sympatry and temporal synchrony on the western slope of the Andes in Peru. Male and female adults of basistrigata are redescribed, and a lectotype is designated.